Manajemen Kemahasiswaan di Ma’had ‘Aly Situbondo dalam Meningkatkan Mutu Pendidikan Perguruan Tinggi - Rif’ah , Rif’ah (Jurnal Pendidikan Islam Indonesia, 2017)
Quality of education is the purpose of every educational institution, including Ma'had 'Aly educational institution in Situbondo. Focus of this research are: 1) Recruitment of new students at Ma'had 'Aly Situbondo, 2) Learning management at Ma'had' Aly Situbondo, 3) Evaluation, increase and graduation conducted at Ma'had 'Aly Situbondo. Research Method: The research approach in this research is qualitative descriptive. Sampling techniques are snowball sampling and purpusive sampling. Data collected by interview, observation and documentation. Technical analysis of field data: Data reduction, data presentation and data verification (Milles and Huberman). Result of research: 1) Entrance selection is done very strictly with written test and oral test, 2) management of curricular and extracurricular students, through lectures and outside activities, 3) Assessment are done during learning activity, after learning activity, middle test and final test every semesters with written and oral tests.